Effect of hypertonic saline in the management of elevated intracranial pressure in children with cerebral edema: A systematic review and meta-analysis. (March 2021) - Afroze, Farzana; Sarmin, Monira; Kawser, CA; Nuzhat, Sharika; Shahrin, Lubaba; Saha, Haimanti; Jahan Shaly, Nusrat; Parvin, Irin; Bint-e Sharif, Mohsena; Mamun, M Al; Ahmed, Tahmeed; Chisti, Mohammod Jobayer
Objective: To determine the hypertonic saline efficacy in children with cerebral edema and raised intracranial pressure. Method: Studies assessing the efficacy and safety of hypertonic saline in children with cerebral edema and elevated intracranial pressure were identified using Medline, Web of Science, Scopus, and Google Scholar databases. Two reviewers independently assessed papers for inclusion. The primary outcome was a reduction of elevated intracranial pressure by the administration of hypertonic saline. Results: We initially evaluated 1595 potentially relevant articles, and only 7 studies met the eligibility criteria for the final analysis. Out of the seven studies, three of them were randomized controlled trials. Three of the studies found that hypertonic saline significantly reduced elevated intracranial pressure compared to control. One study reported a resolution of the comatose state as a measure of reduced intracranial pressure. It also found a significantly higher resolution of coma in the hypertonic saline group rather than the control. Three studies reported that the reduction of intracranial pressure was comparable between the groups. The random-effects model using pooled estimates from four studies showed no difference in hypertonic saline and conventional therapy mortality outcomes. Hypertonic saline was administered as bolus-only therapy at a rate of 1–10 mL/kg/dose over 5 min to 2 h and or bolus followed by infusion therapy (0.5–2 mL/kg/h). One study reported a twofold faster resolution of high intracranial pressure following hypertonic saline administration compared to controls. The re-dosing schedule varied greatly in all included studies. However, three studies reported adverse events but not methodically, and there were no reports on neurological sequelae. Conclusion: Hypertonic saline appears to reduce intracranial pressure in children with cerebral edema. However, we cannot draw a firm conclusion regarding the safest dose regimens of hypertonic saline, including the safe and effective therapeutic hypernatremia threshold in the management of raised intracranial pressure with cerebral edema. Future clinical trials should focus on the appropriate concentration, dose, duration, mode of administration, and adverse effects of hypertonic saline to standardize the treatment.